NON-PHARMACOLOGICAL THERAPY FOR CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD): A SYSTEMATIC REVIEW - Imam, Nurul; Darmawan, Taufan Citra; Alfianti, Khalifatus Zuhriyah; Aga, Maria Sofia Anita; Dianita, Eka Mei; Fernanda, Pradita Ayu; Rusmeni, Ni Putu Diah Ayu (Universitas Nahdlatul Ulama Surabaya, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) is one of the leading causes of death worldwide. This disease attacks the respiratory tract, resulting in chronic symptoms such as narrowing of the airways, shortness of breath, and coughing. However, the management of treatment for this disease is still very lacking. Therefore, the best treatment needs to be understood. Objective: This review article aims to explain the best treatment for COPD sufferers. Design: This study employed a systematic review design guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Data Sources: A comprehensive literature search was conducted using four electronic databases—Scopus, PubMed, Science Direct, and Google Scholar—focusing on articles published between 2020 and 2025. Keywords used included